Moderation Effects of Power Distance on the Relationship Between Types of Empowerment and Employee Satisfaction. (February 2013) - Fock, Henry; Hui, Michael K.; Au, Kevin; Bond, Michael Harris
Previous research concludes that empowerment is ineffective with employees from societies high in power distance. The present study examines this conclusion across three types of empowerment: discretion empowerment, psychological empowerment, and leadership empowerment (or empowerment leadership behaviors). To assess the effects of power distance on these three types of empowerment, employee surveys were conducted in Canada (a society low in power distance) and in China (a society high in power distance). Results showed that the effect of discretion empowerment on employee satisfaction was less pronounced in China, just as previous literature had concluded about the dynamics of societies high in power distance. However, the effect of the leadership empowerment on employee satisfaction via the competence facet of psychological empowerment was found to be more pronounced in Canada, a society lower in power distance. These conclusions at the cultural level were also confirmed at the psychological level. We thus advocate that empowerment remains an advantageous strategy to organizations in both societies and individuals high and low in power distance, depending on the type of empowerment involved.